” in schwedischer und dänischer Übersetzung - Birkmann, Thomas (Folia Scandinavica Posnaniensia, 2007)
The article discusses the very frequent occurrence of indirect (reported) speech in Grass’ novel Der Butt. It presents strategies which have been chosen by the Swedish (resp. Danish) translator of the novel. By means of graphemic, syntactic, lexical and other indicators the translation substitutes the morphological category of subjunctive in the original text. Nevertheless it fails quite often to indicate clearly whether the construction in question is reported speech or the author’s commentary.